Foreign nursing students: Their profile and perceptions of nursing care in Namibia - Louis Small; Louise Pretorius (AOSIS, 2010)
A survey was conducted using open and close-ended questions to determine how visiting nursing students in Namibia could be assisted during their visits (cultural encounters). Many students decide to complete their clinical exposure in a foreign country, either for personal reasons or in order to meet the course requirements for transcultural nursing. Since 1998, Namibia has received a number of these students. In discussion and from passing remarks from the students themselves, the question has arisen as to how an optimum placement for each student might be achieved. Aspects of the Campina-Bacote model and The Process of Cultural Competence in the Delivery of Health Care Services were used to answer this question. It was decided to gather both biographical (profile) information and information on perceptions of nursing care in Namibia from such foreign nursing students. The biographical (profile) information collected indicates a prevalence of certain shared biographical characteristics among international students. Such students tend to be adventurous, caring and sensitive to human rights issues. This finding correlates with the constructs of cultural desire and cultural awareness as described in the model of Campina-Bacote. Based on this finding, specific recommendations were made for clinical allocations. From the data gathered from the open-ended questions, three themes emerged: firstly, nursing in Namibia has identifiable characteristics; secondly, there is a paternalistic and one-sided communication style among nursing caregivers in Namibia; and finally, nursing care delivery in this country is often characterised by a detached attitude. It was concluded that these themes correlated with a cultural awareness and cultural knowledge among the nursing students. The discovery of these themes was useful for making recommendations for clinical guidelines to help these students adapt, as well as for providing a foundation and substantiation for clinical placement. Opsomming 'n Opname bestaande uit oop en geslote vrae is uitgevoer om te bepaal hoe besoekende verpleegstudente aan Namibië ondersteun kan word (kulturele ervarings). Baie studente besluit om hulle kliniese praktika in die buiteland te voltooi, óf om persoonlike redes óf om aan kursusvereistes in transkulturele verpleging te voldoen. Sedert 1998 het Namibië 'n aantal van hierdie studente ontvang. Uit gesprekke met sowel as spontane kommentaar deur hierdie studente het die vraag ontstaan hoe hulle optimum plasing verseker kan word. Aspekte van die model van Campina-Bacote, naamlik The process of cultural competence in the delivery of health care services , is benut om hierdie vraag te beantwoord. Daarom is besluit om biografiese inligting sowel as inligting oor die studente se persepsies van verpleging in Namibië in te samel. Die biografiese inligting (profiel) het die voorkoms van sekere biografiese kenmerke onder die internasionale studente getoon: Hulle neig daartoe om avontuurlik, deernisvol en sensitief vir menseregte te wees. Dié bevinding korreleer met die konstrukte van kulturele begeertes en kulturele bewustheid soos beskryf in die model van Campina-Bacote. Op grond van hierdie bevindinge is bepaalde aanbevelings aangaande hulle kliniese plasings gemaak. Die data deur die oop vrae verkry het drie temas gegenereer, naamlik dat verpleging in Namibië bepaalde identifiseerbare kenmerke openbaar, dat 'n paternalistiese en eensydige kommunikasiestyl onder verpleegkundiges in Namibië voorkom en dat verpleegsorg deur 'n onbetrokke houding gekenmerk word. Die gevolgtrekking was dat hierdie temas met 'n kulturele bewustheid en kulturele kennis onder die verpleegstudente korreleer. Die identifisering van hierdie temas was bruikbaar as basis vir die motivering van kliniese plasings en in die maak van aanbevelings ten opsigte van kliniese riglyne om die studente te help om aan te pas.